“Yeni Terörizm”in Geleceğin Güvenlik Ortamına Etkileri: Daeş Örneği - Selim KURT (Gazi Akademik Bakış)
Terrorism is not a modern phenomenon, although it is often engaged in the international political agenda, especially in the post-Cold War world. There is no doubt that the terrorist attack carried out by the nineteen Al-Qaida militants against the United States on September 11, 2001 was a complete breaking point for terrorism. After this point, motivation sources and methods of the terror, which was started to called as “new terrorism” with its new organization structure and applications, has been changed dramatically. First of all, it is seen that new terrorist organizations have started to be organized in the form of loose horizontal networks with minimum chain of command. Secondly, it is observed that the terrorist organizations in this wave of terror have increased their interest and demand for access to weapons of mass destruction as well as conventional weapons compared to their predecessors. Also it can be said that this new wave of terror is ideologically based on mystical and religious motivations. On the other hand, these new terrorist organizations use unusual asymmetric methods to maximize casualties in their actions. In addition, it is seen that these organizations are specialized in the use of new communication tools such as social media in parallel with technological developments. Undoubtedly, it can be said that ISIS become one of the most important representative of new terrorism in terms of used methods and implemented tactics in the such an environment that new terrorism debates began to be held more intensively following to the September 11 attacks. In this context, the effects of the “new terrorism” to future security environment was analyzed in this study through the DAESH terrorist organization, which is one of the best examples of the new terror definition.